Sexualities research : critical interjections, diverse methodologies, and practical applications - king,Andrew,Ed; Santos, Ana Cristina,Ed; Crowhurst, Isabel,Ed (Routledge advances in critical diversities, 2017)
How is sexuality studied methodologically? How are we innovating, methodologically, in the study of sexuality? What impact, if any, has the increase in mixed methodologies had on the study of sexuality?